PEMBENTUKAN KARAKTER ANAK MELALUI TEATER GAMES - Tafsir Huda (Abdi Seni, 2020)
In the community, the childrend of the village of Drono in the Tembarak sub-district of Temanggung, have low discipline and show a fairly high attitude or ego, like freedom and do not want to be bound or reluctant to be burdened with issues of education. Their character is less formed as a creative soul in expressing their emotions.These characters in the theory of multiple intelligences are referred to as low intrapersonal intelligence. Namely, the low ability of a person in shaping self-quality related to independence, understanding self-potential, asense of responsibility and self-confidence and creativity in expressing his emotions. The low intrapersonal intelligence, will have more complex problems in living community life and tend to be formed into children who are passive and less creative.Creativity is a talent that is potentially owned by everyone, which can be identified and developed through effective and afficient learning. Based on the assumption that children are active theory builders, the learning process while playing is theright model. Playing techniques drama or theater games offer a fun and exciting approach to the learning and teaching process, as well as reciprocal relationships in skills training. Theater games are created to explore one’s potential and explore their active andcreative abilities in responding to and overcoming problems they face. This sensitivity will be manifested in the formof actions and reactions, both personally and in groups.Theater gameand teaching process, as well as reciprocal relationships in skills training. Theater games are created to explore one’s potential and explore their active andcreative abilities in responding to and overcoming problems they face. This sensitivity will be manifested in the formof actions and reactions, both personally and in groups.Theater games triggered by Viola Spolin will be taught as a method of forming children’s characters in Drono village, Tembarak sub-District, Temanggung, through simple and practical forms of theater games but very important for the development of cognitive intelligence, social intelligenceand the formation of children’s personality. Theater games learning isrealized through steps: Preparation, Learning and Evaluation Activities, by choosing the type of game: Energy (heating) Game, asepting (acceptance) Game, Association (association of imagination) Game and Core training.Learning activities through theatrical game training canbroaden social interaction and develop social skills, namely learning to share, living together with mutual respect and respect, learning to take part in community life in general. In addition, the resultsachieved will be able to improve physical development, body coordination, and develop and sharpen the sensitivity of gross and fine motor skills.Keywords: Intrapersonal Intelligence, Creativity, Theater Games.